Development of receptive vocabulary and verbal intelligence in Japanese children with unilateral hearing loss. Issue 3 (June 2022) - Takeyama, Takaaki; Shimada, Aki; Sakamoto, Yuki; Aoki, Toshihito; Kondo, Eiji; Nakano, Seiichi; Fukuda, Junya; Azuma, Takahiro; Sato, Go; Okamoto, Hidehiko; Kitamura, Yoshiaki; Udaka, Jiro; et al.
Abstract: Objective: In the past, it was believed that unilateral hearing loss has a minimal impact on the speech and language development in children. However, several studies have suggested that some school-age children with unilateral hearing loss have learning impairments in language. In the present study, we first examined whether preschool-age children with unilateral severe-to-profound hearing loss (UHL) have delays in the development of receptive vocabulary and verbal intelligence. In the follow-up study, we tested the children again after school admission. The objective of the present study was to reveal the development of receptive vocabulary and verbal intelligence from preschool to school years in children with UHL. Methods: Fifteen Japanese preschool-age children with UHL and a control group of 20 age-matched Japanese children with bilateral normal hearing (NH), who were examined because articulation disorder was suspected, were enrolled in this study. The development of receptive vocabulary and verbal intelligence was evaluated using the Picture Vocabulary Test-Revised (PVT-R) and the Wechsler Intelligence Scale, respectively. The present retrospective study was approved by the Committee for Medical Ethics of Tokushima University Hospital (#3801). Results: The scaled score (SS) of the PVT-R and verbal intelligence quotient (VIQ)/verbal comprehension index (VCI), but not performance intelligence quotient/perceptual reasoning index in children with UHL were significantly lower than those in the control children with NH at preschool-age. The SS of the PVT-R and VIQ/VCI in children with UHL significantly improved after school admission. In the subgroup analysis, the SS of the PVT-R in the lower receptive vocabulary group of children with UHL at preschool-age was significantly increased after school admission, but the SS in the normal and higher receptive vocabulary group of children with UHL at preschool-age were still around the standardized mean of SS after school admission. Conclusion: These findings suggest that the development of receptive vocabulary and verbal intelligence was delayed in preschool-age children with UHL and that most of them caught up to exhibit normal language ability after school admission.